Uptake of cancer risk management strategies among women who undergo cascade genetic testing for breast cancer susceptibility genes. Issue 19 (22nd June 2021) - Makhnoon, Sukh; Tran, Grace; Levin, Brooke; Mattie, Kristin D.; Dreyer, Brian; Volk, Robert J.; Grana, Generosa; Arun, Banu K.; Peterson, Susan K.
Abstract : Background: Uptake of cancer risk management based on inherited predispositions, which encompasses bilateral mastectomy (BLM), bilateral salpingo‐oophorectomy (BSO), and intensified screening, is the primary motivation for cascade testing for hereditary breast and ovarian cancer (HBOC). However, long‐term outcome data for cascade testers are lacking. Methods: Medical records were abstracted for all unaffected women with pathogenic variants in HBOC genes from 2 cancer hospitals (2013‐2019) with at least 1 year of follow‐up to compare the uptake of surgery and screening between cascade and noncascade testers. Results: Cascade testers (79.8%) were younger than noncascade testers (mean age, 37.6 vs 43.5 years; P = .002). Among women aged ≥40 years, 43% underwent BLM, and 71.6% underwent BSO, with no significant difference in uptake between cascade and noncascade testers. The mean time to BSO among cascade testers was shorter among women aged ≥40 years versus those aged <40 years (11.8 vs 31.9 months; P = .04); no such difference was observed among noncascade testers. Mammography and breast magnetic resonance imaging rates were low in the recorded 6 years for both groups after genetic counseling. Conclusions: Management uptake among cascade testers is high with rates comparable to those for unaffected BRCA‐positive women. A large proportion of women act on cascade test results, and this represents a novel report of utilization of cancer management strategies. Abstract : This study compares the long‐term uptake of cancer risk reduction strategies between cascade and noncascade genetic testers. The authors identify high uptake of cancer risk reduction strategies among cascade testers with rates comparable to those of unaffected BRCA‐positive women. This represents a novel report of health care utilization in this population.